MEMBANGUN LITERASI KRITIS PADA GEN ALPHA (MELALUI TEKNOLOGI) DALAM PENGOLAHAN INFORMASI DENGAN MENANAMKAN BUDI PEKERTI - Mardiana Anjani Alamsyah; Lailatul Hidayati; Ach. Barizi; Miko Fitri Ana; Daroe Iswatiningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Generation Alpha is those aged 1 to 14 years old. They are the generation that grew up in the digital age. The Alpha Generation has extensive access to information through technology. However, they tend to lack the ability to sort, analyze, and process information critically. This is a major challenge in the midst of the swift flow of information that has not been validly verified. This research aims to build critical literacy in Generation Alpha through a technology-based approach integrated with ethical values. The research method is descriptive qualitative. This research explores critical literacy through the application of digital learning media in instilling ethical values, responsibility, and social awareness. The results show that technology can be an effective tool to improve critical literacy with an approach based on character strengthening. The cultivation of ethical values through technology-based learning activities can strengthen critical thinking skills, as well as build moral awareness in Generation Alpha. This study recommends the integration of an ethics-based digital literacy curriculum to prepare Generation Alpha to face the challenges of the digital era in the future.